2002
DOI: 10.1073/pnas.062413299
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the thyroid hormone receptor α1 prevents the structural alterations of the cerebellum induced by hypothyroidism

Abstract: Thyroid hormone (T3) controls critical aspects of cerebellar development, such as migration of postmitotic granule cells and terminal differentiation of Purkinje cells. T3 acts through nuclear receptors (TR) of two types, TR␣1 and TR␤, that either repress or activate gene expression. We have analyzed the cerebellar structure of developing mice lacking the TR␣1 isoform, which normally accounts for about 80% of T3 receptors in the cerebellum. Contrary to what was expected, granule cell migration and Purkinje cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
146
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 43 publications
16
146
1
3
Order By: Relevance
“…Indeed, removal of all TRα isoforms rescues the Pax8KO mice from death [69,70]. Deletion of the TRα1 gene also prevents the development of cerebellar abnormalities during TH deprivation [71]. The aporeceptor does not seem to be required for the upregulation of TSH.…”
Section: Combined Tr and Related Gene Deletionsmentioning
confidence: 99%
“…Indeed, removal of all TRα isoforms rescues the Pax8KO mice from death [69,70]. Deletion of the TRα1 gene also prevents the development of cerebellar abnormalities during TH deprivation [71]. The aporeceptor does not seem to be required for the upregulation of TSH.…”
Section: Combined Tr and Related Gene Deletionsmentioning
confidence: 99%
“…For instance, Bernal and coworkers could show that the cerebellar development in TRalpha1 null mice is not altered even when the animals are rendered hypothyroid (Morte et al, 2002). Moreover, in primary cerebellar cultures, dendritic development of Purkinje cells that do not express TRalpha1 was equally advanced independent of the presence of thyroid hormone whereas Purkinje cells of wildtype animals exhibit only poor dendritic growth if thyroid hormone is not added to the medium (Heuer and Mason, 2003).…”
Section: Role Of Thyroid Hormone Receptorsmentioning
confidence: 99%
“…Upon hormone binding, the receptors (holoreceptors) exchange corepressors for coactivators and activate transcription (2). This repressive effect of aporeceptors has been clearly documented in hypothyroid mice for TR␣ in brain, bone, intestine, spleen, and heart (3,4). These observations suggested that the conversion of TR aporeceptors into holoreceptors as a result of a change in T3 concentration in vivo might act as a molecular switch under physiological conditions.…”
mentioning
confidence: 92%
“…It is already well known that T3 plays a critical role during this period, regulating the maturation of different organs such as bone, brain, and intestine. All these events are severely impaired in mice devoid of TRs (8)(9)(10)(11)(12) and in hypothyroid mice (3,4). Heart function is critically controlled by T3 in the adult where hypothyroidism and hyperthyroidism respectively induce bradycardia and tachycardia (1).…”
mentioning
confidence: 99%